Mengurangi Resiko Genangan Air dan Penggunaan Pupuk Kimia dengan Teknik Biopori: Reducing the Risk of Waterlogging and Chemical Fertilizer Use with Biopore Techniques - Para, SM. Andika; Aurelia, Salsabilla; Wabula, Syahfril; Nurlette, Syafina Tunnaja; Kastella, Siti Soraya; Sari, Wa; Lesnussa, Widya Yanti; Laimbo, Anggrina Leondri Sayuti; Silaban, Bernita Br. (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Hative Besar is one of the villages in Teluk Ambon District, Ambon City, which contributes to agricultural production in Ambon. However, a common challenge farmers face during the rainy season is that agricultural lands often become waterlogged, and if the rainfall is intense, many plants rot. Additionally, farmers tend to prefer chemical fertilizers over organic fertilizers, despite the availability of organic waste. This community service aims to educate farmers in Hative Besar village about biopori in reducing the risk of waterlogging and chemical fertilizers. The method used in this service is lectures in the form of socialization and training. The target audience is farmers in Dusun Kamiri, Hative Besar village. Based on the activity results, the level of interest in biopori is very high. Before the activity, participants' knowledge about biopori was only 10%. After attending the socialization and training, the percentage increased to 100%, with a 90% improvement in participants' skills, from not knowing to knowing. This increase in knowledge is expected to help farmers in Hative Besar village reduce excessive water accumulation, which has the potential to damage plant growth, as well as reduce the use of chemical fertilizers.